Advertisements
Advertisements
प्रश्न
Expand.
(a + 2) (a − 1)
उत्तर
It is known that,
(x + a) (x + b) = x2 + (a + b)x + ab
(a + 2) (a − 1) = (a)2 + {2 + (−1)}a + (2) × (−1)
= a2 + (2 − 1)a + (−2)
= a2 + 1a − 2
= a2 + a − 2
संबंधित प्रश्न
Expand.
(m − 4)(m + 6)
Expand.
`(x + 1/x)(x - 1/x)`
Use the Identity (x + a) (x + b) = x2 + (a + b)x + ab to find the following:
95 × 103
Expand: `(m + 3/2)(m + 1/2)`.
Expand (2n – 1)(2n + 3)
Using the identity (x + a)(x + b) = x2 + x(a + b) + ab, find the following product
(6a + 9)(6a – 5)
Using suitable identities, evaluate the following.
10.1 × 10.2
The following expression is the area of a rectangle. Find the possible length and breadth of the rectangle.
x2 – 6x + 8
The following expression is the area of a rectangle. Find the possible length and breadth of the rectangle.
x2 + 19x – 20